2015
DOI: 10.1016/j.jnoncrysol.2015.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between density of metallic glasses and dynamic fragility of metallic glass-forming liquids

Abstract: We study the density evolution upon isothermal annealing far below the glass transition temperature of various metallic glasses (MGs) with different fragilities. We show that the density variation, which reflects the structural heterogeneity of MGs, has correlations with the Poisson's ratio and the kinetic fragility of their supercooled liquid state. The found relationship between the structure heterogeneity of metallic glasses and dynamic heterogeneity of their supercooled liquids has implications for underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Physical aging (or structural relaxation below the glass transition temperature Tg) in metallic glasses is always linked to modifications of physical, mechanical properties and densities [42][43][44][45]. In order to study the influence of physical aging on the evolution on mechanical properties in the La65Al14(Cu5/6Ag1/6)11(Ni1/2Co1/2)10 and Cu46Zr45Al7Y2 metallic glasses, an in-situ DMA testing was carried out at 385 K for the La-based and 660 K for the Cu-based metallic glasses.…”
Section: Physical Aging On the Metallic Glass Below Tgmentioning
confidence: 99%
“…Physical aging (or structural relaxation below the glass transition temperature Tg) in metallic glasses is always linked to modifications of physical, mechanical properties and densities [42][43][44][45]. In order to study the influence of physical aging on the evolution on mechanical properties in the La65Al14(Cu5/6Ag1/6)11(Ni1/2Co1/2)10 and Cu46Zr45Al7Y2 metallic glasses, an in-situ DMA testing was carried out at 385 K for the La-based and 660 K for the Cu-based metallic glasses.…”
Section: Physical Aging On the Metallic Glass Below Tgmentioning
confidence: 99%
“…Aside from the structural metrics above, other structure parameters may also show correlation with the liquid fragility, such as the peaks in pair distribution functions (PDFs), [71][72][73] volume or density variations, 74,75 bond orientational order 76 and interatomic repulsion softness. 77 In a nutshell, these structural indicators suggest that the liquid fragility does correlate with how and how fast the local structural ordering takes place upon cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter ˜= d °+ • ⁄ g ±²² is related to the concentration of flow units, in which and ° are both constants at a given aging temperature. It was found that when • = 0, ˜= d °⁄ g ±²² , which corresponds to the initial concentration of flow units in the as-cast state [336]. Vickers micro-hardness of Zr52.5Cu17.9Ni14.6Al10Ti5 amorphous alloy with annealing time at 600 K [337].…”
Section: Understanding Relaxation Dynamics From the Perspective Of De...mentioning
confidence: 99%
“…The flow unit model was built based on the concept of structural heterogeneity and the concentration of flow units can be correlated with various overall properties of metallic glass, such as density, elastic constants, recovered enthalpy and fictive temperature. In addition, the evolution of flow units, which is linked to the structural heterogeneity of metallic glass, can be described by the density change during thermal annealing below the glass transition temperature Tg [155,335,336]. On the 101 basis of the flow unit model, an empirical function for the time dependence of the physical properties of annealed metallic glass is given as follows [335][336][337][338] (as seen in Fig.…”
Section: Understanding Relaxation Dynamics From the Perspective Of De...mentioning
confidence: 99%
See 1 more Smart Citation